Association between healthy lifestyle and the risk of ischemic stroke among elderly adults with hypertension: a cross-sectional study in China - Wu, Jian; Jiao, Xiaoyu; Qi, Wenzhe; Zhao, Lipei; Guo, Xinghong; Dai, Nengguang; Liu, Rongmei; Zhao, Qiuping; Miao, Yudong; Tarimo, Clifford Silver; Ye, Beizhu (Frontiers in Nutrition, 2025)
IntroductionWhile adopting multiple healthy lifestyle behaviors has been shown to significantly reduce the risk of ischemic stroke (IS) in the general adult population, there is limited evidence on whether such benefits extend to older adults with hypertension. This study aimed to examine how a combination of modifiable healthy lifestyle behaviors is associated with the risks of IS among hypertensive patients aged 65 years and older.MethodsThis population-based study was conducted in Jia County, Henan Province, from 1 July, 2023 to 31 August, 2023. Data on participants’ lifestyles were collected through structured, face-to-face interviews. A composite lifestyle score was generated using five modifiable behaviors: non-smoking, non-drinking, ideal sleep duration, adherence to a healthy diet, and engagement in regular physical activity. The relationship between lifestyle and IS was determined using logistic regression models, with results presented as odds ratios (ORs) and 95% confidence intervals (CIs). To identify optimal interaction patterns among multiple factors, we applied generalized multifactor dimensionality reduction (GMDR) analysis.ResultsA total of 17,747 participants were included (42.11% male, mean age 73.39 years), 31.20% of whom had a history of IS. In multivariable-adjusted models, maintaining a healthy diet, never smoking, getting adequate sleep, and never drinking were each independently associated with a lower risk of IS. There was a clear inverse relationship between the number of healthy lifestyle behaviors and IS risk. After adjusting for covariates, participants who adopted all five healthy lifestyle behaviors had the lowest prevalence of IS, with a 58.5% reduction compared to those who reported none of the healthy behaviors. For every additional point gained in the healthy lifestyle score, the risk of IS dropped by 11.2%. The GMDR analysis showed that sleep, diet, and smoking had the most significant interaction with the risk of IS.ConclusionEmbracing healthy lifestyle habits can significantly lower the risk of IS among older adults with hypertension in China. These findings offer valuable guidance for designing targeted lifestyle interventions aimed at preventing stroke in this high-risk population.